The effect of a school library network on student achievement: evidence from Portugal - Amaro, Gonçalo Ferreira (2022)
In this paper, we study the case of a Portuguese school library network that provides both guidance and funding. We estimate the impact of schools integrating this network on student achievement using a Difference-in-Differences approach. Using information from three administrative datasets and from Rede de Bibliotecas Escolares’ website, and focusing on the 4thgrade national exam scores of Portuguese and Mathematics, we find small to no effects of the program on student achievement. However, in our heterogeneity analysis, we found positive effects for students who benefit from social support, highlighting the importance of school libraries for students from low-income backgrounds.